COVID-19 pandemic versus 'infodemic': the lesser evil - Dharshini Kantharuban; Indumini Gunatilake; Chithramali Rodrigo; Bhumini Karunarathna; Ishanka Talagala; Sampatha Goonewardena; Pushpa Jayawardana; Maheeka Seneviwickrama (College of Community Physicians of Sri Lanka, 2020)
No abstract available